Growth and development profile of children at two day care centers in Jakarta - Siti Budiati Widyastuti; Soedjatmiko Soedjatmiko; Agus Firmansyah (Paediatrica Indonesiana, 2005)
Background Working mothers with toddlers are often confusedwith the difficulties of caregiver substitutes. This leads to the con-cern about neglecting their toddlers. Day care centers are expectedto respond by substituting the absent mothers, in order for thechildren’s needs of growth and development to become optimal.Objective To examine the profile of day care centers in correla-tion with growth and development of toddlers, and to understandthe characteristics of facilities for growth and development in tod-dlers at day care centers.Method This cross-sectional study was conducted at the day carecenters (DCC) of the Department of Social Affairs of the Republicof Indonesia Harapan Ibu (HI) in Salemba, Central Jakarta andTeratai in Bekasi from February 1-August 1, 2004.Results There were 106 children enrolled in this study; 47 chil-dren in DCC HI and 59 in DCC Teratai, male:female ratio was 1:1,mostly at age 3.1-5 years. Growth status was measured accord-ing to body weight/age, body height/age, height circumference/age and found good, normal, and proper growth status in 85 chil-dren (80.2%), 48 children (45.3%), 102 children (96.2%), respec-tively. We found good nutritional status in 44 children (41.5%) andnormal developmental status (Denver II) in 81 children (76.4%).Ratio of caregivers to child was 1:10. All children had completeimmunization. No trauma or upper respiratory tract infection wasrecorded as frequent morbidity. Parents’ reasons for relying theirchildren in DCCs were to enable their children to socialize (50children/47.2%), and to allow them to become independent (49children/46.2%).Conclusion DCCs can serve as a safe alternative caregiving sub-stitute based on good growth and development, good nutritionalstatus, also good characteristics facilities